Final Modals, Adverbs and Antisymmetry in Vietnamese - Duffield, Nigel (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 1999)
ABSTRACTThis paper is concerned with the syntax and semantics of Vietnamese constructions in which a modal element appears unexpectedly to the right of the verb-phrase. Prima facie, this distribution presents a challenge to the universalist proposals of Kayne 1995 and Cinque 1998, a challenge that has been addressed in two previous analyses: Duffield 1998 and Simpson 1997, 1998. The present article re-examines the empirical evidence supporting those previous proposals. It is argued that this evidence is insufficient to justify the derivational complexity of either account. A simpler alternative treatment is proposed which takes account of the various grammatical and extragrammatical conditions governing modal placement in Vietnamese, while simultaneously reconciling these distributions with universal principles.